2015
DOI: 10.1097/pas.0000000000000391
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of 3 Histologic Classifications and 3 Staging Systems for Thymic Epithelial Neoplasms and Its Effect on Prognosis

Abstract: Data regarding the prognostic significance of the histopathologic classifications of thymic epithelial neoplasms are contradictory, perhaps reflecting issues in reproducibility. We studied the effect of reproducibility of 3 histopathologic classifications on prognosis and investigated the interobserver agreement on invasion and its effect on staging and prognosis. A total of 456 patients who underwent surgery for thymic epithelial neoplasm at Mayo Clinic Rochester (1942 to 2008) were staged (modified Masaoka, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 25 publications
(35 reference statements)
0
38
0
Order By: Relevance
“…In that study, the agreement among 3 thoracic pathologists from the same institution was almost perfect for the modified Masaoka staging system (j ¼ 0.85, n ¼ 315) and the proposed Moran staging system (j ¼ 0.81, n ¼ 290) and substantial for the proposed IASLC/ITMIG staging system (j ¼ 0.75, n ¼ 81). 4 If evaluating only the T component of the proposed IASLC/ITMIG (n ¼ 297), the agreement was also substantial (j ¼ 0.75). Most common disagreements occurred between encapsulated and minimally invasive tumors, which would correspond to stage I and IIA tumors of the modified Masaoka staging system (15.8% of cases).…”
Section: Evolution Of the Staging Classification Of Thymic Epithelialmentioning
confidence: 85%
See 2 more Smart Citations
“…In that study, the agreement among 3 thoracic pathologists from the same institution was almost perfect for the modified Masaoka staging system (j ¼ 0.85, n ¼ 315) and the proposed Moran staging system (j ¼ 0.81, n ¼ 290) and substantial for the proposed IASLC/ITMIG staging system (j ¼ 0.75, n ¼ 81). 4 If evaluating only the T component of the proposed IASLC/ITMIG (n ¼ 297), the agreement was also substantial (j ¼ 0.75). Most common disagreements occurred between encapsulated and minimally invasive tumors, which would correspond to stage I and IIA tumors of the modified Masaoka staging system (15.8% of cases).…”
Section: Evolution Of the Staging Classification Of Thymic Epithelialmentioning
confidence: 85%
“…Moreover, this study showed that the only moderate to substantial reproducibility of histomorphologic classifications indeed plays a role in determining the prognostic significance of TET, with differences in prognosis between the 3 reviewers in multivariate analysis. 4 Therefore, Roden et al 40 evaluated the prognostic significance of thymoma using cases in which all 3 thoracic pathologists independently agreed upon a diagnosis. Univariate analysis confirmed that all histomorphologic classifications studied, including Bernatz, Suster and Moran, and WHO (2004), are of prognostic significance for overall and disease-free survival.…”
Section: Staging Is Prognostically Superior To Histomorphologic Classmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the histologic classification of posttreatment TETs was difficult because the histologic type might be biased on account of treatment effect as well as heterogeneity of TETs and interobserver variability, which we have shown previously. 19 Second, differences in neoadjuvant treatment occurred not only between studies but also within studies, including ours. Given the rarity of the tumor, these differences were unavoidable because to achieve a larger number of cases, these had to be collected over many years.…”
Section: Discussionmentioning
confidence: 74%
“…Because of interobserver variability in the morphologic classification of TETs, 19 all pre-and postneoadjuvant treatment specimens were reviewed by three thoracic pathologists (A. C. R., M. C. A., and E. S. Y.).…”
Section: Pathology Reviewmentioning
confidence: 99%